O superior interesse da criança no processo de adoção nacional - Tiago, Catarina Alexandra Duarte (2021)
The present Thesis is set within the context of the Curricular Internship carried out at the Family and Juvenile Court of Lisbon, where I first became acquinted with adoption as a mean of protection for children forlorn of a family environment wherein they can grow up healthy. Based on the aforementioned and acknowledging the child as a subject of rights highlights that it is entitled to have its best interest taken into consideration and respected, not only in the final decisions that concern it, but also during the entire decision-making process. This is the case with the adoption process, one which greatly affects the life of the child, for which both parts involved, adoption applicant ad adoptee, in particular, have to undergo countless procedures of assessment, profiling, preparation, and interaction. Thusly, said thesis to shed light on how the child’s best interests manifest throughout the adoption process and ascertain if they indeed play a leading role therein.